The DARPA Robotics Challenge Finals: Humanoid Robots To The Rescue - Spenko, Matthew; Buerger, Stephen; Iagnemma, Karl.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The DARPA Robotics Challenge was a robotics competition that took place in Pomona, California USA in June 2015. The competition was the culmination of 33 months of demanding work by 23 teams and required humanoid robots to perform challenging locomotion and manipulation tasks in a mock disaster site. The challenge was conceived as a response to the Japanese Fukushima nuclear disaster of March 2011. The Fukushima disaster was seen as an ideal candidate for robotic intervention since the risk of exposure to radiation prevented human responders from accessing the site.  This volume, edited by Matthew Spenko, Stephen Buerger, and Karl Iagnemma, includes commentary by the organizers, overall analysis of the results, and documentation of the technical efforts of 15 competing teams. The book provides an important record of the successes and failures involved in the DARPA Robotics Challenge and provides guidance for future needs to be addressed by policy makers, funding agencies, and the robotics research community.    Many of the papers in this volume were initially published in a series of special issues of the Journal of Field Robotics. We have proudly collected versions of those papers in this STAR volume. .
The DARPA Robotics Challenge Finals: Results and Perspectives -- Robot System of DRC-HUBO+ and Control Strategy of Team KAIST in DARPA Robotics Challenge Finals -- Team IHMC's Lessons Learned from the DARPA Robotics Challenge: Finding Data in the Rubble -- Developing a Robust Disaster Response Robot: CHIMP and the Robotics Challenge -- DRC Team NimbRo Rescue: Perception and Control for Centaur-like Mobile Manipulation Robot Momaro -- Team RoboSimian: Semi-autonomous Mobile Manipulation at the 2015 DARPA Robotics Challenge Finals -- Director: A User Interface Designed for Robot Operation with Shared Autonomy -- Achieving Reliable Humanoid Robot Operations in the DARPA Robotics Challenge: Team WPI-CMU's Approach -- Team DRC-Hubo@UNLV in 2015 DARPA Robotics Challenge Finals -- Team SNU's Control Strategies to Enhancing Robot's Capability: Lessons from the DARPA Robotics Challenge Finals 2015 -- Team THOR's Entry in the DARPA Robotics Challenge Finals 2015 -- Collaborative Autonomy Between High-level Behaviors and Human Operators for Control of Complex Tasks with Different Humanoid Robots -- WALK-MAN Humanoid Platform -- An Architecture for Human-Guided Autonomy: Team TROOPER at the DARPA Robotics Challenge Finals -- Team VALOR's ESCHER: A Novel Electromechanical Biped for the DARPA Robotics Challenge -- Perspectives on Human-Robot Team Performance from an Evaluation of the DARPA Robotics Challenge -- What Happened at the DARPA Robotics Challenge Finals.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Control, Robotics, Automation; Artificial Intelligence